Scale for the evaluation of visitor experiences in a shopping center in Cali, Colombia (International Journal of Scientific Research and Management (IJSRM), 2022)
This article presents the reliability and validity of a scale that evaluates the experiences of visitors to the shopping center in Cali - Colombia. The methodology is framed within a quantitative, descriptive, and causal approach, through the application of the hypothetical-deductive method. The variables considered in the measurement scale were determined from a theoretical review and content validation. To collect the information, a personal survey was administered to a sample of 343 customers. The validity and reliability of the scale was determined by Exploratory Factor Analysis, Cronbach’s coefficient, and Confirmatory Factor Analysis. Among the main findings, it is highlighted that the scale shows high reliability and internal consistency since one factor explains 50% of the total accumulated variance and the total Cronbach’s Alpha is 0.846. When the confirmatory model was applied, positive correlations were identified between the indicators and the variables and between the three variables. Therefore, the final scale consisted of three: subscales emotional experiences, sensory experiences, cognitive experiences, and 23 items.